Navigating Faith Online: Social Media and Religious Literacy among Women's Religious Groups - Iskandar, Dudi; Suratno, Geri; Raharjo, Didik Haryadi (Fakultas Dakwah UIN Saizu Purwokerto, 2025)
The integration of social media into religious practices exhibits a complex dichotomy. On one side, social media is primarily driven by the principles of virality, popular appeal, and commercial interests. Conversely, religious traditions emphasize silence, peace, and tranquillity. Initially, social media served as a communication medium and enhanced religious knowledge within communities. However, its use has evolved towards cultivating personal and collective identities. The passion to increase religious knowledge and gain religious experience is disrupted by the desire for artificial physical appearances shared in social media groups. This research aims to describe and analyze the use of social media among recitation women in Tangerang, Banten. This research utilized observation, interviews, and intertextuality as data collection and analysis techniques. This study indicates that the engagement of recitation women with social media necessitates religious and social media literacy. A lack of proficiency in these areas could adversely affect the quality of social media interactions, as social media platforms are inherently non-neutral and are influenced by particular ideologies and interests. Consequently, recitation women must adopt a discerning and critical approach to assess the incoming and disseminated content on social media.